Tinea Corporis - Wina Adelia Pasaribu; Malahayati Malahayati (Lembaga Pengembangan Kinerja Dosen, 2025)
Approximately 35.4% of the Asian population suffers from Tinea corporis, a superficial dermatophyte fungal infection that attacks hairless skin such as the face, arms, and legs. This dermatophyte causes symptoms in the form of circular lesions with active red and scaly edges and a calmer center. This case involved a 12-year-old girl who came to the Dermatology and Venereology Polyclinic of Fauziah Bireun Hospital with complaints of reddish spots on her body that had lasted for eight months. The lesions were accompanied by itching, especially when sweating or in hot conditions, but improved after bathing. The clinical diagnosis showed Tinea corporis. The therapy given was 2% ketoconazole cream applied twice a day and systemic treatment with 200 mg itraconazole and 10 mg cetirizine. This management aims to overcome fungal infections, reduce symptoms, and prevent recurrence. Patient education regarding personal hygiene and prevention of skin moisture is an important part of therapy.